Revision of the genus Eusyllis Malmgren, 1867 (Annelida: Phyllodocida: Syllidae: Eusyllinae), with the description of a new species from the eastern Pacific Ocean - Brusa, Vivian S.; Aguado, Maite Teresa; San Martín, Guillermo; Rouse, Greg (Zootaxa, 2013)
Eusyllis Malmgren, 1867 (Annelida, Syllidae) is revised, with 7 species considered as valid (Eusyllis assimilis Marenzeller, 1875; Eusyllis blomstrandi Malmgren, 1867; Eusyllis kupfferi Langerhans, 1879; Eusyllis lamelligera Marion & Bobretzky, 1875; Eusyllis longicirrata Imajima, 1966; Eusyllis maxima (Monro, 1930); and Eusyllis nuchalata Hartmann-Schröder, 1965) plus a newly described species (Eusyllis grandmarie n. sp.) the only species of the genus recorded from a whale carcass, lying at more than 600 m deep in the eastern Pacific Ocean off the California coast. The new species is characterized by elongated compound chaetae, with blades almost unidentate, and a thin, spine-like proximal tooth. It differs from Eusyllis longicirrata Imajima, 1966, from Japan, in having shorter dorsal cirri and blades of compound chaetae. Additionally, Eusyllis nuchalata Hartmann-Schröder, 1965 is re-described. A key to the species of the genus is included.